ショウワ キチ エンガン カラ ミズホ カンソク キョテン ニ イタル チイキ ノ キショウ ジョウタイ ニ ツイテ - 山田, 知充; ヤマダ, トモミ; YAMADA, Tomomi (国立極地研究所, 1974)
P(論文) The lapse rates of air temperature were found to be 0. 7℃/100m in the austral summer and 1. 1～1. 2℃/100m in winter while the annual mean air temperature decreases with increasing the elevation at the rate of 1. 1℃/100m in this region. An amplitude of a diurnal variation of air temperature at Mizuho Camp in summer was about 5℃ and the maximum and the minimum of air temperature was observed about 1500 (LMT) and 0300. In winter, the temperature varied with the period of 5～7 days with an amplitude of 7～13℃. The variation of air temperature and atmospheric pressure measured at many observation sites distributed along the traverse route were closely correlated in phase with those measured at Syowa Station. The stationary katabatic wind blew in this region and the 5 minute mean wind speed was between 10m/s～20m/s throughout the year, but it was reduced to less than 10 m/s for a short period in summer season. The wind speed measured at Mizuho Camp in summer showed a daily variation with an amplitude of approximately 2～3 m/s, and the phase of the variation was shifted from that of the diurnal variation of air temperature. The wind direction was observed to be very stationary between ENE and ESE throughout the year in this area. The types of weather observed during oversnow traverses and the stay at Mizuho Camp were only blowing snow, snow and clear ・ fine ・ cloudy. At Mizuho Camp, blowing snow was not observed when the wind speed was less than 7 m/s, and high blowing snow was always observed above 14 m/s. departmental bulletin paper